A Preliminary Investigation of School Counselors' Attitudes and Behaviors Toward Research and Professional Information Seeking. Issue 1 (6th September 2021) - Belser, Christopher T.; Mason, Erin C. M.
To investigate what school counselors read for professional information seeking and how they engage with research, we surveyed practicing school counselors about their behaviors, attitudes, and beliefs toward engaging with school counseling-related information resources. The findings highlight gaps between the usage of newer web-based resources and traditional research and identified potential incongruence between school counselors' beliefs about engaging with research and their actual behaviors. We provide implications for school counselor training and professional development.